Characterization of raw and ozonated oil sands process water utilizing atmospheric pressure gas chromatography time-of-flight mass spectrometry combined with solid phase microextractionun. (March 2021) - Huang, Rongfu; Yang, Lingling; How, Zuo Tong; Fang, Zhi; Bekele, Asfaw; Letinski, Daniel J.; Redman, Aaron D.; Gamal El-Din, Mohamed
Abstract: This work describes a novel application of atmospheric pressure gas chromatography time-of-flight mass spectrometry (APGC-TOF-MS) combined with solid-phase microextraction (SPME) for the simultaneous analysis of hydrocarbons and naphthenic acids (NAs) species in raw and ozone-treated oil sands process water (OSPW). SPME method using polydimethylsiloxane (PDMS)-coated fibers was validated using gas chromatography with flame ionization detector (GC-FID) to ensure the SPME extractions were operated appropriately. The ionization pathways of the hydrocarbon species in OSPW in the APGC source were verified by analyzing a mixture of eight polyaromatic hydrocarbons which were ionized primarily via charge transfer to produce [M + ] while NAs in OSPW were found to be ionized through protonation to generate [MH + ] in the wet APGC source. SPME/APGC-TOF-MS analysis demonstrated a different composition profile in OSPW #1, with 74.5% of hydrocarbon species, 23.4% of O2 –NAs, and 2.1% of the oxidized NA species at extraction pH 2.0 compared with that obtained by UPLC-TOF-MS analysis (36.9% of O2 –NAs, 26.8% of O3 –NAs, 24.9% of O4 –NAs, 9.1% of O5 –NAs, 2.3% of O6 –NAs). Moreover, the peak areas of the total NAs and the total peak areas of NAs + hydrocarbons measured by SPME/APGC-TOF-MS correlated excellently with the total NA concentration determined by UPLC-TOF-MS (R 2  = 0.90) and the concentrations of the total acid-extractable organics determined by SPME/GC-FID (R 2  = 0.98), respectively. APGC-TOF-MS integrated with the SPME techniques could extend the range of target compounds and be a promising alternative to evaluate and characterize NAs and hydrocarbon in different water types. Graphical abstract: Image 1 Highlights: SPME coupled with APGC-TOF-MS was used for analysis of hydrocarbons and NAs. PDMS fibers preferably extracted neutral organic compounds at natural pH. The PDMS fibers extracted hydrocarbons and some protonated NAs species at pH 2.0 PAHs were ionized via charge transfer while NAs were ionized through protonation. Ox -NAs peak areas by SPME/APGC-TOF-MS correlated to the Ox -NAs by UPLC-TOF-MS.